Online interactive language utilities for Bangla and English using PHP script and adobe flash technology - Hasan, Shiblee Imtiaz (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2010.